2020
DOI: 10.1111/jpc.15240
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of falls in children from windows and balconies: What has changed?

Abstract: Aim To describe patterns of injury from window and balcony falls in children presenting to a tertiary paediatric trauma centre in New South Wales. Methods A retrospective review of cases of children <15 years who had sustained injuries in a fall from a building, identified from the trauma database between 1998 and 2019. Results A total of 381 falls from windows and balconies were recorded over the 22‐year study period. There were 218 falls from windows (57%) and 163 from balconies. The majority (64%) were chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The findings of this review regarding the type and severity of injuries caused by falls from windows are in line with literature. Similar to past studies, here we also observed that falls from windows led to major trauma and identified skull fractures, lacerations, abrasions and contusions as the most common injuries [ 11 ]. Furthermore, we also recorded patients that had sustained injuries leading to intracranial bleeding but exhibited high GCS scores at presentation.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this review regarding the type and severity of injuries caused by falls from windows are in line with literature. Similar to past studies, here we also observed that falls from windows led to major trauma and identified skull fractures, lacerations, abrasions and contusions as the most common injuries [ 11 ]. Furthermore, we also recorded patients that had sustained injuries leading to intracranial bleeding but exhibited high GCS scores at presentation.…”
Section: Discussionsupporting
confidence: 89%
“…In Singapore, the Tanjong Pagar Community Development Council started a scheme in 2000 called “ Prevent the Fall ” which paid and installed window grilles in the homes of low-income families (Au Yong, 2000). Despite these campaigns, children falling from windows and balconies remain a problem in both Sydney (Houlton et al , 2020) and Singapore. To prevent falls, the Building Code of Australia for new buildings was amended in June 2013 to restrict the opening of windows to a maximum of 12.5 cm where the floor below the window is more than 2 m above the surface beneath (Houlton et al , 2020).…”
Section: Children Falling From Windows and Balconies: The Fixing Of S...mentioning
confidence: 99%
“…Despite these campaigns, children falling from windows and balconies remain a problem in both Sydney (Houlton et al , 2020) and Singapore. To prevent falls, the Building Code of Australia for new buildings was amended in June 2013 to restrict the opening of windows to a maximum of 12.5 cm where the floor below the window is more than 2 m above the surface beneath (Houlton et al , 2020). There are also requirements in relation to the height and openings in balustrades at balconies (Yusuf et al , 2015).…”
Section: Children Falling From Windows and Balconies: The Fixing Of S...mentioning
confidence: 99%
“…[1] Motor vehicle crashes are the most common cause of injury-related deaths, followed by falls, both in developed countries and developing countries. [2][3][4][5] After injury, injured cells/ tissues release an alarmin (damage-associated molecular patterns, DAMPs), causing a local pro-inflammatory reaction. The local production of alarmins could lead to systemic inflammation, [6,7] resulting in many bimolecular changes after injury, including white blood cell (WBC), interleukin 6 (IL-6), tumor necrosis factor α (TNF-α), fibrinogen (FIB), C-reactive protein (CRP) and procalcitonin (PCT).…”
Section: Introductionmentioning
confidence: 99%